Acute-phase administration of ivabradine supported by intra-aortic balloon pump induces myocardial recovery without significant haemodynamic worsening in a patient with acute fulminant myocarditis: a case report. Issue 8 (12th August 2022) - Ando, Moriyasu; Watanabe, Naoki; Saku, Keita; Morishima, Itsuro
Abstract: Background: Ivabradine can reduce the heart rate without affecting myocardial contractility or vascular tone. Current guidelines recommend its use for treating patients with chronic heart failure who have a high heart rate (≥75 b.p.m.) and persistent symptoms despite guideline-directed therapy. Nonetheless, little is known about its efficacy in patients with acute cardiogenic shock. We report a case of successful treatment of cardiogenic shock Case summary: A 53-year-old previously healthy man was admitted due to cardiogenic shock with acute fulminant myocarditis. The patient was placed on intra-aortic balloon pump support and was given guideline-directed therapy including inotropic agents and furosemide. However, no improvement was seen in haemodynamics and the patient was in sinus tachycardia (116 b.p.m.). On Day 2, ivabradine therapy was initiated to reduce the myocardial workload and stabilize the haemodynamic parameters. As heart rate decreased, his symptoms improved and urine output increased without affecting the blood pressure. Subsequently, the patient recovered from cardiogenic shock. The intra-aortic balloon pumping was discontinued on Day 7, and the patient was discharged on Day 22. Discussion: Ivabradine has the potential to induce rapid cardiac recovery and haemodynamic improvement in the acute phase of heart failure if supported by intra-aortic balloon pump.